Sanur as a Motivational Stage: Exploring the Dynamics of Freelancers in the Gig Economy of the Tourism Sector - Udariani, Pande Made Arnesia; Gorda, Anak Agung Ngurah Oka Suryadinatha (International Journal of Economics Development Research (IJEDR), 2025)
In an environment where many workers operate as freelancers or independent contractors, work motivation becomes the main driver for maintaining service quality and business sustainability. Motivation also plays an important role in promoting innovation and renewal in the tourism industry, as motivated workers tend to look for ways to improve the quality of their services. This research aims to determine the main motivational factors that influence freelancers in the tourism gig economy and the dynamics of the gig economy that influence the motivation and work experience of freelancers in Sanur. The Sanur Tourism Area, which is located on the southeast coast of Bali Island, which is one of the most sought-after tourist destinations in Indonesia, is the place used in this research. The researcher used a qualitative method. Data collection in this research was through observation, documentation, and interviews with informants who had been determined using purposive sampling techniques. The conclusion obtained is that the main motivating factor for freelancers in the Sanur tourism sector is income. Income becomes a central element that motivates them to engage in the dynamics of the gig economy, influencing their decisions to choose certain projects and determining their level of involvement in freelance work.